Infections in gynecology and obstetrics. Selection and apparent flaws in the antimicrobial treatment. - Gutiérrez Aparicio, Carlos (2015)
Infectious diseases can be described as a clash between pathogens and the body's resistance factors. The antimicrobial appear, such as penicillin, streptomycin, tetracycline, etc., it was thought that this could be the end of the struggle between man pathogens and germs; but problems arose that denied this claim.